Exodontia curriculum evaluation: fit for purpose teaching and learning strategies - Behardien, Nashreen; Titus, Simone; Roman, Nicolette V. (Frontiers in Education, 2024)
Introduction: Curriculum review is crucial for ensuring health professions education programs remain responsive and relevant. Teaching and learning (T&L) strategies facilitate knowledge acquisition, with traditional methods being supplemented by innovative techniques in a blended curriculum. This study evaluated an Exodontia Block Course (EBC) focused on tooth extraction skills, utilizing a blended-learning approach across three learning environments: classroom, preclinical skills laboratory, and clinical training platform. Methods: A qualitative study employed appreciative inquiry for data collection and analysis. Focus group discussions were conducted with 30 participants: 13 undergraduate students, 10 clinical teachers, and 7 dental practitioners. Data underwent coding and thematic analysis. Results: Two main themes relevant to this paper emerged: "Block course structure" and "Recommendations for improvement." Participants affirmed the blended-learning approach, highlighting strengths like demonstrations, videos, activity workbooks, and assessments that supported learning. Recommendations included integrating more visual technologies, simulated patients, peerlearning, debriefing, case reviews, community-based learning, and dedicated skills Commented [N1]: Replace with: Exodontia curriculum evaluation: Fit for purpose teaching and learning strategies laboratories. Discussion: While the traditional course adequately achieved its objectives, opportunities for enhancement were identified. Incorporating advanced educational technologies, simulation-based activities, and structured feedback mechanisms could optimize skills development. Real-world clinical experiences and peer-assisted learning may reinforce knowledge and foster competencies like clinical reasoning. Continued curriculum refinement through stakeholder feedback is essential for delivering effective, student-centered dental education, and by inference, improved patient care.